Investigating Master One EFL learners’ Oral Presentation and Its Impact on Peers - Lounis Kenza, Yousfi Nadjah (UNIVERSITY OF MOHAMED BOUDIAF, 2022)
Abstract This study is about the effect of master one’s oral presentation on their peers, the aim from this study is to find out what kind of effect oral presentation has on students who are attending an oral presentation performed by fellow students as well as their level of understanding lectures presented this way. While researching there were no research found on this specific topic of the effect of students oral presentation on the audience that is fellow students therefor this study adopted the exploratory research method and the data was collected using a questionnaire that consists of 18 yes or no questions and 2 multiple choice questions . Regarding the current style of teaching during the scholar year 2021/2022 that makes the contact time with students limited it is hard to categorize students with appropriate questionnaire for each category therefor a large sample of over 40% (50 students) of the students in master one English department was chosen however only 41 questionnaires were returned for that reason the study collected data from these 41 questionnaires. After a deep analysis of the data the results were that most students agree that they understand about 50% meaning half of the lectures and topics presented via oral presentation performed by classmates this means we cannot say oral presentation is positive or negative but that there is room for improvement, some suggestions were given to help with said improvements such as using oral presentation for certain subjects and not for whole lectures.
Keywords: Key Words: oral presentation, exploratory research, level of understanding, questionnaire